Practical synthesis of isocoumarins via Rh(III)-catalyzed C–H activation/annulation cascade - Gao, Qian-Ci; Li, Yi-Fei; Xuan, Jun; Hu, Xiao-Qiang (Beilstein Journal of Organic Chemistry, 2023)
Herein, we report an unprecedented Rh(III)-catalyzed C–H activation/annulation cascade of readily available enaminones with iodonium ylides towards the convenient synthesis of isocoumarins. This coupling system proceeds in useful chemical yields (up to 93%) via a cascade C–H activation, Rh-carbenoid migratory insertion and acid-promoted intramolecular annulation. The success of gram-scale reaction and diverse functionalization of isocoumarins demonstrated the synthetic utility of this protocol.
Keywords: C–H activation; enaminone; iodonium ylide; isocoumarin; rhodium catalysis